The impact of digital transformation on media industry. (26th October 2022) - Costa, Renato Lopes da; Cabral, Luis; Pereira, Leandro; Dias, Álvaro; Gonçalves, Rui
The media industry is currently in the process of adapting digital transformation. As the industry is increasing its volume, due to the fact that the consumers are consuming more media than before, it is important to guarantee the fulfilment of consumer needs. After the literature review, the present article studied the opinions of some authors through a questionnaire that was used to comprehend the benefits that the digital transformation brought to the media industry, as well as understand how consumer behaviour has changed over the past years. In this sense, a new consumption style was identified, which is the involuntary one, where people really do not have the intention of using a content. To sum it up, the present article pretends to characterise the media industry and the consumer behaviour, in a digital context, where processes must be changed in order to adapt to imminent changes.